2016
DOI: 10.1371/journal.pgen.1005967
|View full text |Cite
|
Sign up to set email alerts
|

Competition between Jagged-Notch and Endothelin1 Signaling Selectively Restricts Cartilage Formation in the Zebrafish Upper Face

Abstract: The intricate shaping of the facial skeleton is essential for function of the vertebrate jaw and middle ear. While much has been learned about the signaling pathways and transcription factors that control facial patterning, the downstream cellular mechanisms dictating skeletal shapes have remained unclear. Here we present genetic evidence in zebrafish that three major signaling pathways − Jagged-Notch, Endothelin1 (Edn1), and Bmp − regulate the pattern of facial cartilage and bone formation by controlling the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
108
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(117 citation statements)
references
References 115 publications
(142 reference statements)
9
108
0
Order By: Relevance
“…Hierarchical clustering of transcriptome data grouped the two independent nr2f2; nr2f5 mutant samples with a previously published Edn1-misexpressing sample, whereas the Nr2f5-misexpressing sample clustered with two edn1 mutants (Fig. 4B) (Barske et al, 2016, Askary et al, 2017). Thus, Nr2fs and Edn1 act oppositely to regulate both jaw molecular identity and skeletal composition/morphology.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Hierarchical clustering of transcriptome data grouped the two independent nr2f2; nr2f5 mutant samples with a previously published Edn1-misexpressing sample, whereas the Nr2f5-misexpressing sample clustered with two edn1 mutants (Fig. 4B) (Barske et al, 2016, Askary et al, 2017). Thus, Nr2fs and Edn1 act oppositely to regulate both jaw molecular identity and skeletal composition/morphology.…”
Section: Resultsmentioning
confidence: 79%
“…Less is known about upper jaw regulation. Although Jagged-Notch signaling restricts mandibular gene expression in parts of the upper first and second arches, maxillary-derived portions of the upper jaw develop normally in zebrafish and mice with reduced Jagged-Notch signaling (Zuniga et al, 2010, Humphreys et al, 2012, Barske et al, 2016, Teng et al, 2017). Six1 mutant mice show a partial transformation of the posterior end of the maxilla into a mandible-like structure, but this phenotype is attributable to an upstream role for Six1 in limiting Edn1 expression within the dorsal pharyngeal endoderm (Tavares et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Its functional network (Fig 9B) shows that 7 of its 9 genes are involved in gene expression, including four transcription factors involved in OFCs, Barx1, Dlx1, Lhx8 and Sim2, as well as Lhx6 and the histone deacetylase co-repressor complex members Mab21l1 and Mab21l2. Four of these 9 genes are involved in establishing the dental lamina (Denaxa et al, 2009; Grigoriou et al, 1998; Mitsiadis and Drouin, 2008), while Ndnf, Mab21l2, Lhx6, Lhx8b, Barx1 and probably also Dlx1a are regulated by the interaction of the Edn1 and Notch signaling pathways that restricts cartilage primordia in the upper face in zebrafish (Barske et al, 2016). Because there is no obvious role of the dental lamina in earlier facial morphogenesis, we interpret this module as a jaw patterning program, possibly specific to the maxilla.…”
Section: Resultsmentioning
confidence: 99%
“…In a genetic screen in zebrafish, we previously identified a loss-of-function mutation in the JAG1 homolog, jag1b , which resulted in specific malformations of the palatoquadrate and hyomandibular cartilages 3 . Subsequently, we found that Jag1b works through the Notch2 and Notch3 receptors to regulate bone and cartilage differentiation in the dorsal portions of the mandibular and hyoid arches, regions from which the incus and stapes bones arise in mammals 4 . We therefore asked in this study whether loss of Jagged-Notch signaling might similarly disrupt development of the stapes and incus bones.
Figure 1Craniofacial and middle ear defects in mice deficient for Jag1 or Notch2 .
…”
Section: Introductionmentioning
confidence: 98%